Politizace pracovníků ministerstev v České republice dle pracovních pozic: současná teorie a praxe - Jan Kohoutek; Martin Nekola (Sociální studia, 2017)
The article analyses perceptions of the nature and extent of politicization by officials at eleven ministries of the Czech Republic. The empirical part of the article is based on a large-N inquiry among ministerial officials that were divided into four groups (directors of section, directors of department, heads of division, rank-and-file officials) following their work position. From the theory perspective, the article builds upon two types of politicization – formal and functional – with the latter further subdivided into hidden and partisan politicization. Such theoretical assumptions help towards formulating six hypotheses verified with relation to the four work positions. The corresponding analysis of officials’ perceptions by position attests to a rather limited extent of the two main types of politicization with the exception of functional politicization of top management (director of section). Compared to the other three positions, directors of section show more proclivity to personal contacts (functional-hidden politicization) or to direct party political nomination (functional-partisan politicization). Unlike the conclusions of previous, largely expert or qualitative, inquiries, the officials’ perceptions generally point towards rather moderate politicization of the Czech ministries without excessive direct influence of political representatives.